Negligible seeding source effect on the final ANAMMOX community under steady and high nitrogen loading rate after enrichment using poly(vinyl alcohol) gel carriers. (October 2018) - Cho, Kyungjin; Choi, Minkyu; Lee, Seockheon; Bae, Hyokwan
Abstract: This study investigated the effect of seeding source on the mature anaerobic ammonia oxidation (ANAMMOX) bacterial community niche in continuous poly(vinyl alcohol) (PVA) gel systems operated under high nitrogen loading rate (NLR) condition. Four identical column reactors packed with PVA gels were operated for 182 d using different seeding sources which had distinct community structures. The ANAMMOX reaction was achieved in all the bioreactors with comparable total and ANAMMOX bacterial 16S rRNA gene quantities. The bacterial community structure of the bioreactors became similar during operation; some major bacteria were commonly found. Interestingly, one ANAMMOX species, " Candidatus Brocadia sinica", was conclusively predominant in all the bioreactors, even though different seeding sludges were used as inoculum source, possibly due to the unique physiological characteristics of " Ca . Brocadia sinica" and the operating conditions (i.e., PVA gel-based continuous system and 1.0 kg-N/(m 3 · d) of NLR). The results clearly suggest that high NLR condition is a more significant factor determining the final ANAMMOX community niche than is the type of seeding source. Graphical abstract: Highlights: Four up-flow bioreactors inoculated with different seeding sludges were compared. High NRR was established in the bioreactors with comparable ANAMMOX gene quantity. The bacterial community structures of the reactors became similar during operation. " Candidatus Brocadia sinica" became absolutely predominant in the bioreactors. Seeding source effect on final ANAMMOX community was negligible.